Inverse Vehicle Dynamic Model of a Bicycle Vehicle with Power Steering: A Bond Graph Approach - Anshuman (My University, 2014)
As the traffic is increasing day by day the possibility of accidents are increasing. These accidents are due to the human errors. Development of inverse dynamic controller necessary as it can replace the driver and track the predefined path. A bond graph model of a bicycle vehicle is developed and in this model manual and electrical power steering systems are attached and a comparison of both systems for evaluating the response is done. An inverse vehicle dynamics model is developed. This inverse model gives a torque to a bicycle model to follow a predefined path. An expression is derived to compute the steering angle in terms of longitudinal velocity and vehicle yaw rate for a predefine path. The inverse vehicle dynamics model is connected by an overwhelming controller in such a way that the output of forward model is feedback to inverse bicycle model. The vehicle’s position is compared with the desired trajectory and the error signal is given to the inverse bicycle model to produce the desired output.
ME-CAD/CAM-Dissertation
Keywords: Bicycle model; Bond graph modelling; Electrical power steering; Ghost controller; Inverse bicycle model; Manual steering; Overwhelming controller